The Development of the Cooperative Banking Sector in Selected Central and Eastern European Countries - Nowacka, Anna (Comparative Economic Research. Central and Eastern Europe, 2024)
The study assesses the development of the cooperative banking sector in selected Central and Eastern European (CEE) countries against the average statistics of the segment in those countries. It also compares it to the largest European cooperative banking group in Germany. The article presents the results of an analysis of the cooperative banking sectors between 2016 and 2021 in Poland, Bulgaria, Romania, Hungary and Germany, all of which are members of the European Association of Cooperative Banks (EACB). The selection criterion was based on the availability of detailed data on cooperative banks published by the EACB on a temporal and spatial basis. The empirical basis for the issues addressed in the article is a review of the reference literature and the comparative analysis of the development of the cooperative banking sector using a synthetic development indicator for the period 2016–2021. According to the theoretical and empirical analysis, Romania demonstrates the lowest level of development of the cooperative banking segment. In turn, the Polish and Bulgarian cooperative banking sectors represents a higher level of development than the Romanian one. Hungary has reached the highest level of development in the group of Central and Eastern European countries. While comparing the CEE countries to the German cooperative banking sector, their development was almost one and a half times lower and, in the case of Romania, three times lower.